Perspectivas de la filosofía analítica en el siglo XXI - Bustos Guadaño, Eduardo De (Revista de Filosofía, 2007)
A relatively close account of the evolution of analytical philosophy shows that never enjoyed an unique methodology nor a common set of theses. In particular, if we understand that by ‘analytical philosophy’ we refer to a wider philosophical movement than the ‘ordinary language philosophy’, such lack of methodological or substantial coherence is even more evident. Then, it can be asked whether a conceptual description of analytical philosophy at the beginnings of XXI century is possible. As it is proposed, such description is only feasible under an axiological basis, that is, under the commitment with a set of scholar values that give a minimal consistency to philosophical analysis such it is practised nowadays. The nature of those values can be included, generally speaking, in the realm of the epistemological, but what is concretely contended is that it is mandatory to pay attention to its discursive and argumentative nature. This shift of focus allows to surpass the virtues and flaws of analytical philosophy in the 20 nth century and facilitates the re evaluation of its function in the 21 nth one.